The economic impact of recreational trails: a systematic literature review - Lukoseviciute, Goda (2022)
Recreational trails are a type of nature-based tourism providing various activities such as hiking, biking, rafting or horseback riding. Increasing investment in infrastructure and touristic services development has resulted in higher visitor expenditure and thus contributed to economic development. This study aims to review the current economic impact assessment studies on recreational trail tourism and to extract the main economic impact determinants. A systematic literature review analysis was applied in a quantitative approach about economic models, study cases of nature-based tourism, comparison of economic impacts. A qualitative analysis was then applied with an inductive approach to compare the economic impacts of nature-based tourism forms and identify the main determinants of economic impact. This study suggests that I-O is the most suitable theoretical approach to study the economic impact of long-distance trails, while the Keynesian multiplier approach and Ad hoc model are the most suitable approaches to study the economic impact of short-distance trails.